2016
DOI: 10.1098/rsos.150541
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine responses in birds challenged with the human food-borne pathogenCampylobacter jejuniimplies a Th17 response

Abstract: Development of process orientated understanding of cytokine interactions within the gastrointestinal tract during an immune response to pathogens requires experimentation and statistical modelling. The immune response against pathogen challenge depends on the specific threat to the host. Here, we show that broiler chickens mount a breed-dependent immune response to Campylobacter jejuni infection in the caeca by analysing experimental data using frequentist and Bayesian structural equation models (SEM). SEM pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 64 publications
3
50
1
1
Order By: Relevance
“…The RNA level of expression was determined by qPCR using the Roche Diagnostics LightCycler 480 (Hoffmann La Roche AG, Switzerland). The primers sequence for GAPDH, INF , IL-1 , IL-4, IL-6, IL-10, IL-17A, IL-17F, ChCXCLi1 and ChCXCLi2 (74,75,76) are presented in Supplementary Table 4. Cytokines and chemokines transcripts fold change were calculated according to the manufacturer's recommendation using the 2 - Ct method (77).…”
Section: Rna Isolation and Rt-qpcr Of The Cytokines And Chemokinesmentioning
confidence: 99%
“…The RNA level of expression was determined by qPCR using the Roche Diagnostics LightCycler 480 (Hoffmann La Roche AG, Switzerland). The primers sequence for GAPDH, INF , IL-1 , IL-4, IL-6, IL-10, IL-17A, IL-17F, ChCXCLi1 and ChCXCLi2 (74,75,76) are presented in Supplementary Table 4. Cytokines and chemokines transcripts fold change were calculated according to the manufacturer's recommendation using the 2 - Ct method (77).…”
Section: Rna Isolation and Rt-qpcr Of The Cytokines And Chemokinesmentioning
confidence: 99%
“…Adaptive responses to C. jejuni are poorly described in the literature, and there is a lack of functional studies of adaptive immunity in the chicken. Cytokine responses that drive cellular, humoral and Th17 responses are found in the gut following infection678, and antibody responses to infection and specific antigens including LPS, LOS and flagella have been described previously91011. Furthermore, various experimental vaccines have produced specific antibody responses, although none have been found to be fully protective or able to elicit protection via a strategy that is cost effective for the poultry industry1213141516.…”
mentioning
confidence: 99%
“…In the present study, network analyses detected interferon signalling among the pathways associated with resistance. Interferon-γ (IFN-γ) has been reported to be induced following Campylobacter infection of avian cells [54] and chickens in a breed-dependent manner [55], and may underlie breed-specific differences in gut inflammation and pathology [20, 56]. Furthermore, multiple interferon-related genes were found to be differentially expressed in the caecal transcriptome of chickens with high and low C. jejuni colonisation levels in a previous RNA-Seq study [16].…”
Section: Discussionmentioning
confidence: 99%
“…Our pathway analysis also showed enrichment for other innate and adaptive immune related pathways in association with Campylobacter resistance. Of increased interest is the pathway related with IL-17 signalling since several previous studies suggested that IL-17 signalling and T H -17 responses play a role in resistance to Campylobacter colonisation in chickens following experimental inoculation [13, 16, 19, 56, 63, 64]. Future studies could seek to characterise the timing and magnitude of such responses in birds of predicted resistant or susceptible genotypes upon exposure.…”
Section: Discussionmentioning
confidence: 99%